Pengembangan Aplikasi Sistem Pemesanan Digital Berbasis QR Barcode Menggunakan Metode Prototyping - Sutawijaya, Bernard Limasta; Kurniawan, Rido Dwi (STMIK Banjarbaru, 2026)
Digital transformation at Can Ngopi Coffee Shop is urgently needed to address queue bottlenecks and manual recording errors in traditional systems. This study aims to analyze the implementation of a QR Barcode-based digital ordering system to enhance service efficiency. System development utilizes the Prototyping method, encompassing analysis, design, construction, and testing phases. Validation was conducted through User Acceptance Testing (UAT) and essay questionnaires for customers and managers. Testing results indicate that all functional features of the system, integrated with Point of Sales (POS), were accepted and functioned optimally. The system is proven effective in accelerating transaction processes, minimizing data errors, and improving the service quality of culinary MSMEs in the digital era.Keywords: QR Barcode; Prototyping; Service Efficiency; MSMEs, Point of Sales.